Právní regulace související s výrobky v kontextu cílů Evropské unie v oblasti ochrany klimatu - Tereza Fabšíková (Acta Universitatis Carolinae. Iuridica, 2024)
This paper examines how objectives of the European Union in the field of climate change affect the legal regulation of products and what impacts they also have on some connected issues. The current ecodesign legal regulation is based on the Ecodesign Directive and the particular requirements on products are then set in regulations following the Ecodesign Directive. The paper primarily focuses on the changes in ecodesign product regulation brought by the new Ecodesign for Sustainable Products Regulation proposal. The issue of the proposed legal regulation connected with environmental claims is also addressed in the text as it is an important complement to the sustainable products legal regulation.